FAKTOR PELAKSANAAN KANGAROO MOTHER CARE PADA BAYI BBLR - Tri B. Lestari; Yuni S. Arief; NK A. Armini (Universitas Airlangga, 2014)
Introduction: Until recently, Low Birth Weight Babies (LBWB) has become an issue in Indonesia which causes morbidity and mortality during neo-natal period. A common problem found on LBWB is instable body temperature. An effort to solve this problem is done by treating LBWB in incubators. However, the limited incubator facility increases hypothermia on LBWB. Kangaroo Mother Care (KMC) treatment is very effective to solve this problem. This research aims to understand the factors related to Kangaroo Mother Care (KMC) implementation on LBWB at Dr. Soetomo General Hospital nursery room. Method: This is a descriptive analytical research using cross-sectional approach. The sample of this research was the mothers of low birth weight babies being treated at nursery room of Dr. Soetomo General Hospital, Surabaya which consists of 15 respondents determined by inclusion criteria. The data were collected using questionnaire and observations on the respondents. Statistical test used in this research was spearman rho correlation test with p≤ 0.05 as the significance level.Result: The findings of this research indicated that KMC was well implemented at the nursery room of Dr. Soetomo General Hospital, Surabaya. There was a significant relationship between mothers’ knowledge and the implementation of KMC (p=0.027; r=0.567), and a significant relationship between mothers’ attitude and the implementation of KMC (p=0.027; r=0.643). There was also a significant relationship between family support and the implication of KMC (p=0.032; r=0.554).Discussion: It can be concluded that better knowledge, attitudes, and support on kangaroo mother care can improve the implementation of KMC on mothers with low birth weight babies. Mothers’ attitude is the dominant factor on Kangaroo Mother Care (KMC) implementation. As the suggestion, further researches should involve more respondents in order to obtain more accurate result.